Managerial Competence, GHRM dan Green Accounting terhadap Keberlanjutan Ekowisata - Satria, Mohd Rhana; Sari, Rizki Yuli (Jurnal Informatika Ekonomi Bisnis, 2025)
This study aims to analyze the effect of managerial competence, green human resource management (GHRM), and green accounting on ecotourism sustainability in Community-Based Tourism Groups (Pokdarwis) in the coastal tourism areas of Bintan. The research employed a quantitative approach with a survey method to several Pokdarwis in Bintan. Data were analyzed through validity and reliability tests, as well as multiple linear regression analysis. The findings reveal that managerial competence and green accounting particularly in recording and managing conservation costs have a significant positive effect on ecotourism sustainability, while GHRM shows a significant negative effect. Simultaneously, the three variables contribute 93.5% to ecotourism sustainability. These results highlight the importance of strengthening managerial competence and optimizing the recording of conservation costs through green accounting, as well as evaluating GHRM practices to make them more effective in supporting ecotourism sustainability.